Nazism as fascism : violence, ideology, and the ground of consent in Germany 1930 - 1945 - Eley, Geoff 1949- (Routledge, Taylor & Francis Group, 2013)
Origins, post-conservatism, and 1933 : Nazism as a breach -- Driving for rule, extracting consent : bases of political order under fascism -- The return of ideology : everyday life, the Volksgemeinschaft, and the Nazi appeal -- Missionaries of the Volksgemeinschaft : ordinary women, Nazification, and the social -- Empire, ideology, and the east : thoughts on Nazism's spatial imaginary -- Putting the holocaust into history : genocide, imperial hubris, and the racial state -- Where are we now with theories of fascism?